Methacrylated gelatin hydrogels as corneal stroma substitutes: in vivo study. Issue 18 (12th December 2019) - Kilic Bektas, Cemile; Burcu, Ayse; Gedikoglu, Gokhan; Telek, Hande H.; Ornek, Firdevs; Hasirci, Vasif
Abstract: Methacrylated gelatin (GelMA) hydrogels were prepared to serve as corneal stroma equivalents. They were highly transparent (ca. 95% at 700 nm), mechanically strong and withstood handling and had high human corneal keratocyte viability (98%) after 21 days of culture period. In order to test the in vivo performance of the cell free GelMA hydrogels a pilot in vivo study was carried out using eyes of two white New Zealand rabbits. Hydrogel was implanted in a mid-stromal pocket created and without suture fixation, and observed for 8 weeks under a slit lamp. No edema, ulcer formation, inflammation or infection was observed in both the control (sham) and hydrogel implanted corneas. Corneal vascularization on week 3 was treated with one dose of anti-VEGF application. Hematoxylin and Eosin staining showed that the hydrogel was integrated with the host tissue with only a minimal foreign body reaction. Results demonstrated some degradation in the construct within 8 weeks as evidenced by the decrease of the diameter of the hydrogel from 4 mm to 2.6 mm. High transparency, adequate mechanical strength, biocompatibility and well integration with the host tissue, indicates that this hydrogel is a viable alternative to the current methods for the treatment of corneal blindness and deserves testing on larger number of rabbits and more extensively using microscopy, histology and immune histochemistry.